PERANCANGAN KAWASAN WISATA ALAM SIPATN LOTUP DI KABUPATEN SANGGAU - Ananda, Nolla; Khaliesh, Hamdil; Nurhamsyah, Muhammad (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
Tourism is an important sector for national revenue, and West Kalimantan holds significant potential, particularly in Sanggau Regency, which features the flagship destination of Sipatn Lotup Hot Springs the only natural hot spring in the province. Strategically located on the border with Sarawak, Malaysia, this site has strong potential to attract both domestic and international tourists. However, inadequate management and a lack of supporting infrastructure have hindered its development. To address these issues, a landscape design approach based on Contextual Architecture is proposed, focusing on environmental harmony and sustainable development. The proposed solution involves dividing the area into six functional zones: reception, management, tourism, commercial, accommodation, and supporting facilities. The design process consists of four main stages: identification of the design object, data collection, analysis and synthesis, and final design development. The objective is to create a tourist area that is comfortable, functional, and sustainable, while maximizing its natural potential. This approach is expected to enhance the quality of the destination and provide long-term benefits to the tourism sector in Sanggau Regency.